Daily usage of smartphone among undergraduates in Malaysia / Noor Mayudia Mohd Mothar - Mohd Mothar, Noor Mayudia (2016)
In today's world smartphones had become an essential item that is almost inseparable from oneself. Young people especially the students are very much rely on this device as it help one to be constantly socially connected to the world as it give access to a lot of information and keep them updated in the happenings around them. This study aims to identify the undergraduates' smartphone pattern of usage for integration and social interaction. Moreover this research sampled 385 Malaysian undergraduates between 18 to 27 years from various public and private universities in Malaysia. Overall the result shows that even when they were apart from their family, they use smartphone to keep in close contact with their family and their loved ones. These findings help to understand the nature of smartphone usage among youth.